1996
DOI: 10.1111/j.1748-5827.1996.tb02353.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with elevated cutaneous Malassezia p a chyderm a tis populations in dogs with Pruritic skin isease

Abstract: The prevalences of breeds and concurrent diseases in a group of 40 dogs with pruritic skin disease associated with elevated cutaneous Malassezia pachydermatis populations were compared with samples of a dermatological hospital population. The ages and genders of the affected dogs were comparable to those of the dermatology population. Basset hounds, cocker spaniels and West Highland white terriers were significantly overrepresented. Concurrent diseases were diagnosed in 27 dogs, of which 15 were atopic. Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
99
1
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(106 citation statements)
references
References 15 publications
1
99
1
3
Order By: Relevance
“…The chi-square analysis revealed that there is a significant difference between male and female dog's in the occurrence of Malassezia dermatitis (P<0.5). In contrary to this study no significant sex predilection for Malassezia infection was detected by Bond et al, (1996) and Nardoni et al, (2004).…”
Section: Spitz 13contrasting
confidence: 53%
See 1 more Smart Citation
“…The chi-square analysis revealed that there is a significant difference between male and female dog's in the occurrence of Malassezia dermatitis (P<0.5). In contrary to this study no significant sex predilection for Malassezia infection was detected by Bond et al, (1996) and Nardoni et al, (2004).…”
Section: Spitz 13contrasting
confidence: 53%
“…The detailed breed wise occurrence of Malassezia dermatitis is presented in Table 3. Certain breeds like American cocker spaniel, Springer spaniel, Basset Hound, Daschund, English setter, West Highland terrier, Silky terrier, German Shepherd, Poodles, Chihuahua and Collie are reported to be at increased risk (Plant et al, 1992, Bond et al, 1996, Maulldin et al, 1997, Charach 1997and Muller et al, 2001. In Puducherry region, most of the middle and low income groups of people were rearing Non descriptive breeds of dogs due to their economic status.…”
Section: Polymerase Chain Reactionmentioning
confidence: 99%
“…There are studies showing high sensitivity of certain breeds, like Basset Hound, Dachshund, Cocker Spaniel, West Highland White Terrier, Poodle and Australian Silky Terrier (Plant et al 1992;Bond et al 1996), in other studies, on contrary, majority of dogs with positive isolates were crossbreeds (Cafarchia et al 2005). For the purpose of evaluation of the results of this study, the dog breeds were divided into groups according to hair type.…”
Section: Discussionmentioning
confidence: 99%
“…The predisposing factors that determine the formation of Malassezia mycoses include: the alteration of the host´s Unauthenticated Download Date | 5/9/18 6:37 AM immune system, greasy skin, high temperature, humidity, corticosteroid treatment and others [2]. Currently, the ge- [7,8].…”
Section: Introductionmentioning
confidence: 99%